A single high‐resolution HLA mismatch has a similar adverse impact on the outcome of related hematopoietic stem cell transplantation as a single low‐resolution HLA mismatch. Issue 7 (July 2015) - Fuji, Shigeo; Kanda, Junya; Kato, Shunichi; Ikegame, Kazuhiro; Morishima, Satoko; Miyamoto, Toshihiro; Hidaka, Michihiro; Kubo, Kohmei; Miyamura, Koichi; Tsudo, Mitsuru; Kobayashi, Hikaru; Maesako, Yoshitomo; et al.
<x xml:space="preserve">Abstract</x> The relative importance of the resolution level of HLA typing has not been fully defined for related donor transplantation. To address this question, we retrospectively evaluated patients who underwent a first related hematopoietic stem cell transplantation (HSCT) from 2000 to 2011 from an HLA high‐resolution matched (MRD, n = 2, 244), high‐resolution 1 locus‐mismatched (HR‐MMRD, n = 116), or low‐resolution 1 locus‐mismatched related donor (LR‐MMRD, n = 396) in the graft‐versus‐host direction at three loci (HLA A, B, and DRB1) using the database of the Japan Society for Hematopoietic Cell Transplantation. The median age was 40 years (0–74). The median follow‐up duration of surviving patients was 950 days. Although the cumulative incidences of grade III–IV acute graft‐versus‐host disease (GVHD) in the HR‐MMRD and LR‐MMRD groups were significantly higher than those in the MRD group (HR‐MMRD 19.8%, LR‐MMRD 20.4%, and MRD 9.5%), there was no statistically significant difference between the HR‐MMRD and LR‐MMRD groups (P = 0.65). Although both HR‐MMRD and LR‐MMRD were significantly associated with an increased risk of non‐relapse mortality and a worse overall survival, there was no statistically significant difference between the HR‐MMRD and LR‐MMRD groups. In conclusion, LR‐MM and HR‐MM have a similar adverse impact on the outcome in related HSCT. Am. J. Hematol. 90:618–623, 2015. © 2015 Wiley Periodicals, Inc.